The Impact of ChatGPT Integration on Arabic Language Learning Among Generation Z Students - Nurfaizah; Muhamad Hasyim; Yanti Puspita; Sumiati; Yuli Azizah; Ummatin Najla; Syifaunupus; Samiah; Yanti Uspita (Formad English Foundation NTB Jakarta, 2026)
This study addresses the limited evidence on the impact of ChatGPT integration on Arabic language learning among Generation Z students, particularly across linguistic, cognitive, motivational, and ethical dimensions. The study aims to synthesize recent evidence on ChatGPT-supported Arabic language learning and identify emerging patterns, challenges, and research gaps. A systematic literature review was employed using a PRISMA-informed approach to identify, screen, evaluate, and synthesize relevant studies published primarily between 2021 and 2026. The literature was analyzed thematically across linguistic development, motivation and engagement, learner autonomy, self-regulated learning, higher-order thinking, AI literacy, personalization, ethical use, and potential dependency. The findings indicate that ChatGPT can support Arabic reading, writing, speaking, grammar, vocabulary, translation, language practice, personalized feedback, motivation, and self-directed learning. Cognitive benefits were also identified when ChatGPT was integrated through structured guidance and active learner engagement. However, concerns regarding academic integrity, dependency, information accuracy, privacy, and inadequate human validation remain. The review concludes that ChatGPT is most effective as a guided human-AI learning support system rather than a replacement for teachers or learners. The study contributes theoretically by integrating technological, cognitive, and learner-centered perspectives and practically by highlighting the need for AI literacy, responsible prompting, teacher guidance, and human verification. Future research should examine Generation Z learners through longitudinal, experimental, and cross-skill studies in Arabic language education.